A Multidisciplinary Approach to Evaluate the Efficiency of a Clean-Up Technology to Remove Mercury from Water - Lopes, Claudia B.
A microporous material denoted ETS-4 was used as the decontaminant agent to treat water with a low level of Hg contamination. The effectiveness of the treatment was evaluated by assessment of the efficiency of Hg removal and ecotoxicological responses. The results showed that under highly competitive conditions the removal of Hg ranged between 58 % and 73 % depending upon the initial Hg concentration, and that Hg removal was reflected in decreased toxicity to some organisms. The ecotoxicological data indicated that the bacterium Vibrio fischeri was the least sensitive organism tested, as no toxicity was observed in either pre- or post-treatment waters. Daphnia magna was highly sensitive to Hg. Mercury removal by ETS-4 was not sufficient to completely remove the toxicity of Hg to D. magna. However, it was effective in the complete reduction of toxicity for the green alga, Pseudokirchneriella subcapitata.